2020
DOI: 10.4028/www.scientific.net/msf.993.1110
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of Zinc Phosphate Conversion Coatings on AZ91D Surface

Abstract: Magnesium alloys have been widely applied in many fields, because of their high strength-to-weight ratio. However, magnesium alloys have high chemical activity and are easily corroded. The poor corrosion resistance of magnesium alloys greatly limits its further application. In this paper, the zinc phosphate conversion coatings were prepared on the surface of AZ91D magnesium alloys. Nano-zinc oxide was the source of zinc and the zinc phosphate conversion coatings were prepared by the given process: 1.25 g/L NaN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…One of the factors limiting the use of this metal is its weak corrosion resistance [11][12][13]. In fact, magnesium metal with a standard potential of −2.34 V vs. NHE (normal hydrogen electrode), when exposed to a corrosive environment, shows weak corrosion resistance and quickly disappears [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors limiting the use of this metal is its weak corrosion resistance [11][12][13]. In fact, magnesium metal with a standard potential of −2.34 V vs. NHE (normal hydrogen electrode), when exposed to a corrosive environment, shows weak corrosion resistance and quickly disappears [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the simplicity in operation and low prices, phosphate conversion coatings being an alternative to chromate conversion coatings are developed [31,32,[37][38][39][40]. Through preparing a manganese phosphate conversion coating (MnPCC) on the Mg-10Li-1Zn alloy (in wt.%) and measuring its corrosion resistance, Zhang et al reported that the MnPCC of Mg alloys had the better corrosion resistance than chromate conversion coatings [33].…”
Section: Introductionmentioning
confidence: 99%
“…This attributes to the decomposition of cellulose and lignin through the dehydration on the polymer side chain during the calcination process. In addition, the peak at 440 °C corresponds to the decomposition of the main chain of cellulose and lignin [28]. Therefore, the slow calcinations of the rice straw undergo a stepby-step thermal decomposition, which makes it fully take advantage of the organism fibril structures as the templates to form the silica fibers.…”
mentioning
confidence: 99%